“Spread one’s wings”: Cognitive-behavioral therapy for reducing interpersonal dependency in female college students - Elmy Bonafita Zahro; Grace Killis; Ina Saraswati (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Interpersonal dependency is a common clinical concern among emerging adult women and is linked to impaired autonomy and relational distress, yet evidence-based interventions in university counseling settings remain limited. This study examined the clinical utility of a brief cognitive behavioral therapy (CBT) targeting dependency-related cognitions and autonomy skills among female undergraduates with dependent personality features. Three students (ages 20–21) recruited from a university counseling service were screened using the dependent personality subscale of the PDQ-4+. A one-group pretest–posttest design with follow-up was employed. Interpersonal dependency was assessed using the Interpersonal Dependency Inventory (IDI) at pre-intervention, post-intervention, and follow-up, supplemented by qualitative clinical evaluation. Participants showed clinically meaningful and sustained reductions in IDI scores, alongside improvements in boundary setting, independent decision making, and emotion regulation. Findings suggest that brief CBT-based interventions may be feasibly integrated into regular university counseling services, while highlighting the need for larger controlled studies.